PAMANESE: KAPAMPANGAN WOMEN AND ETHICS OF CARE (Isagoge - Journal of Humanities and Social Sciences, 2025)
Pamanese is a rich Kapampangan word that on one hand could be translated to “Cook Rice”. On the other hand, as in a deeper sense, it refers to one of the said ethnic group virtues which could be loosely translated to English as “give care” and “nurturing”. The “pamanase” manifests through various kapampangan’s daily life habits such as through family traditions in cooking, cultural values which reflects to as of their cultural identity. Pamanese as showing care towards the “other” adheres to the ethics of care which centers on a belief system that “to give care” is the heart of morality. As Nel Noodings argue, it anchors to the attributes of “being” a woman. This study parallelled Kapampangan’s Pamanese to ethics of care. The researchers explored Kapampangan women’s way of giving care to their social dimension. It was made possible through semi-structured questionnaire that focuses on their cultural practices in giving assistance in their social dimensions as a woman. We explored (I) Kapampangan women’s concept of pamanese. In this sense, we unveiled the limitation and identity of the word “pamanese” (II) Kapampangan women’s actual way of doing pamanese to their social dimension (III) How doing pamanese affects their well-being. The paper used a qualitative approach that gathered quality and detailed data on experiences and concepts from the respondents. Purposive and Snowball sampling were both utilized as we collected data. Thematic analysis that is deductive in nature was utilized in the process of analyzing the data provided by the respondents. This paper used ethics of care as a theoretical framework that leads to establish a philosophical discourse regarding Kapampangan women’s pamanese. The study made a discourse that “pamanese” through its cultural forms is a Kapampangan women’s morality.
Keywords: Cultural Identity; Kapamapangan Women; Ethics of Care; Feminism